The Effect of Quality Perception and E-WOM, Brand Image as Intervening Variable, on UNIQLO Apparel Purchase Decisions in Semarang City - Paras Adwitya Sejati; Siti Sumiati (Komunitas Dosen Indonesia, 2026)
The fashion industry is experiencing intense competition alongside rapid digital transformation, which has influenced changes in consumer purchasing behaviour. The development of e-commerce has become a strategic medium that supports trading activities and facilitates the spread of electronic word of mouth (e-WOM), allowing consumers to access product information more easily. This study aims to analyse the effect of perceived quality and electronic word of mouth on purchase decisions of UNIQLO apparel products in Semarang City, with brand image serving as an intervening variable. This study utilized a quantitative method based on survey responses from 100 customers who had shopped at UNIQLO multiple times. The examination was carried out with the help of Partial Least Squares-Structural Equation Modelling (PLS-SEM). The findings indicate that both perceived quality and electronic word-of-mouth (e-WOM) have a beneficial effect on brand perception and buying decisions. Additionally, while brand image plays a significant mediating role in the connection between perceived quality and purchase choices, it does not serve as a mediator for the connection between e-WOM and purchasing decisions. These findings highlight the necessity of ensuring high product quality and enhancing brand image to improve consumer purchasing choices in the competitive fashion industry. This research adds to the theoretical understanding of consumer behavior and offers practical advice for fashion retailers.